El paradigma positivista, el giro postpositivista y el auge actual de la argumentación jurídica - Abache Carvajal, Serviliano (Revista de Derecho, 2019)
In this paper the positivism and postpositivism paradigmes are reviewed, as well as the actual importance of legal reasoning theory, mainly from Josep Aguiló Regla´s position.